Maqasid Al Syari'ah; Cara Islam Menghadapi Pandemi Covid 19 - Sulaeman, Mubaidi (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2021)
Hundreds of times human life has been visited by epidemics. It is also caused by disease outbreaks that a people have perished and been swallowed up by history. However, the same thing is always repeated, epidemics always come from carelessness caused by human actions themselves. As if not taking the existing lesson, humans naturally have a dichotomous character, apart from having a strong instinct to defend their life, on the other hand, humans have a tendency to do things that lead to their own destruction. Islam as a rational religion is required to provide certainty for problems related to the plague that is shaking the established order of life of Muslims. Islam must be a solution in providing a more definite answer to the direction of Muslim civilization in the covid-19 pandemic season should be built to lead to a new normal era. One answer is to use the perspective of maqasid al-shari'ah in exploring the sources of sharia law to find solutions for Muslims during the Covid-19 pandemic.